The Role of Corresponding Health Workers in Strengthening Infection Control Practices: A Comprehensive Review - Rashdi, Mousa Muflih; Alnomasy, Ashwaq Saud Rabah; Alotaibi, Abdulrahman Mujri Sultan; Alkhalawi, Abdullah Ahmed Abdullah; Al -Harbi, Muhammad Salem Falah; Alrashidi, Adel Hamid; Al-Harbi, Salem Mohammed; Alrashdi, Fahad Hameed Batel; Alqahtani, Shaker Ali Abdullah (Journal of Posthumanism, 2024)
Corresponding health workers play a pivotal role in strengthening infection control practices within healthcare settings. Positioned at the frontline of patient care, these professionals are responsible for implementing critical infection prevention strategies, monitoring compliance, and facilitating communication between departments and infection control units. This comprehensive review explores the core responsibilities, challenges, and enabling factors that influence the effectiveness of corresponding health workers in infection control. Drawing from international guidelines, systematic reviews, and real-world case studies, the article highlights the importance of education, institutional support, and behavior-based interventions. It also examines barriers such as limited resources, training gaps, and organizational culture. The findings emphasize that empowering corresponding health workers through targeted training, leadership engagement, and multidisciplinary collaboration can significantly reduce healthcare-associated infections and improve overall patient safety. The review concludes with actionable recommendations for policy makers, healthcare institutions, and researchers to support and enhance the role of corresponding health workers in infection prevention programs across diverse healthcare contexts.